Paediatric vaccinations: a bibliographic analysis on COVID-19 and influenza - Perrone, Pier Mario; Milani, Gregorio Paolo; Castaldi, Silvana (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Vaccinations represent one of the most effective tools for the prevention of disease, as evidenced by the extensive literature on the subject. With COVID-19, this attention has further increased by centralising scientific production. This study aimed to evaluate and compare the literature on the topic of vaccinations for children, with a focus on the differences between the vaccines for influenza and for COVID-19.Methods: The literature search was conducted by evaluating English-language articles that studied popula-tions under the age of 18 years and excluding non-full papers or articles that did not provide qualitative data. The full-text analysis was conducted for articles published in the three highest IF journals in paediatrics, general medicine and vaccines.Results: The publication timelines show significant diversity with a peak in 2022 for articles concerning the 2019 novel coronavirus (44.6%) and a constant frequency for articles concerning influenza. Concurrently, the populations examined in the studies exhibit minimal divergence, with North America and Europe representing the predominant regions in both groups.Conclusions: In light of the multitude of studies examining efficacy and effectiveness, particularly in the context of COIVD-19, the scientific community should direct its attention to the underlying factors that shape perceptions of vaccines, whether hesitancy or acceptance.